O valor da escala parroquial na análise dos cambios da ocupación territorial na provincia de Pontevedra - Pazo Labrador, Alberto José (Madrygal. Revista de Estudios Gallegos, 2009)
In this paper we suggest the virtuality of the “parroquial” scale for the analysis of territory. We have studied the changes and the reorganization of the population in the province of Pontevedra.
Keywords: “Parroquia”; Density of population; Geographic contrasts; Spatial organization patterns; Cartographic representation